Identification of human plasma proteins associated with the cell wall of the pathogenic fungus Paracoccidioides brasiliensis. Issue 2 (26th March 2013) - Longo, Larissa V.G.; Nakayasu, Ernesto S.; Matsuo, Alisson L.; Peres da Silva, Roberta; Sobreira, Tiago J.P.; Vallejo, Milene C.; Ganiko, Luciane; Almeida, Igor C.; Puccia, Rosana
Abstract Paracoccidioides brasiliensis and Paracoccidioides lutzii are thermodimorphic species that cause paracoccidioidomycosis. The cell wall is the outermost fungal organelle to form an interface with the host. A number of host effector compounds, including immunologically active molecules, circulate in the plasma. In the present work, we extracted cell‐wall‐associated proteins from the yeast pathogenic phase of P. brasiliensis, isolate Pb3, grown in the presence of human plasma and analyzed bound plasma proteins by liquid chromatography–tandem mass spectrometry. Transport, complement activation/regulation, and coagulation pathway were the most abundant functional groups identified. Proteins related to iron/copper acquisition, immunoglobulins, and protease inhibitors were also detected. Several human plasma proteins described here have not been previously reported as interacting with fungal components, specifically, clusterin, hemopexin, transthyretin, ceruloplasmin, alpha‐1‐antitrypsin, apolipoprotein A‐I, and apolipoprotein B‐100. Additionally, we observed increased phagocytosis by J774.16 macrophages of Pb3 grown in plasma, suggesting that plasma proteins interacting with P. brasiliensis cell wall might be interfering in the fungal relationship with the host.